Czy możliwa jest detronizacja amerykańskiej waluty? Dolar po kryzysie z 2008 r. - Sielska, Alicja (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The subject of this chapter is an analysis of the international role of the dollar after financial crisis in 2008. For this purpose, the monetary history of the US over last hundred years was presented first and then causes of the last global crises were analyzed. After this introduction, the current position of the dollar as an international currency was examined, based on available empirical data, and an attempt was made to assess its future by setting three possible scenarios.
Keywords: financial crisis; international currency; United States dollar